Semiotics of Political Caricature in the Palestinian Newspapers An Analytical Study - Turban, Majed Salem (ALBAHITH ALALAMI, 2013)
This study aims to study the political caricature and its indications in the Palestinian newspapers, to know its subjects, the active characters, the artistic styles, and the symbols the caricaturists use. The study concluded that there is a variety of subjects that the political caricature handled in the studied newspapers and the degree of interest in every subject. The subjects related to the international subjects came first (% 24.5) and the other subjects came next (% 22.2). The results showed the caricaturists relied on unnamed symbolic active characters that came first (% 62.3) and named symbolic characters (% 11.1). The positive characteristics of the Palestinian figures were higher than the negative ones, and the negative characteristics of the Palestinian figures are higher than the positive characteristics of the Arab, Israeli, and international figures. Finally, the results showed that the political caricature published in the newspapers of the study indicated a number of artistic styles to show semiotic features through a number of symbols to reveal their meanings and indications.